Mission á ICOM Paris: The ICOM June Meetings 2018 - Roeland P Paardekooper (EXARC, 2018)
The International Council of Museums or ICOM has 41,000 members worldwide, all of which are museum professionals. In a span of six years, ICOM grew from 31,000 to 41,000 members; Europe makes up 84% of members, whilst individual members total to 93%. As a member you are entitled to an ICOM Membership Card, which gives you free entrance to thousands of museums worldwide. Meetings are held annually for the ICOM managers, consisting of board members of the national and international committees. In 2010, EXARC became an affiliated member of ICOM, and was invited to join the group of almost 250 people. Only 40% of ICOM members are member of one of the international committees. ICOM international handles 3.4 million Euro from member’s dues. The largest challenges for 2018 are launching the new website, costing some 126,000 Euro, as well as modifying / repairing the underlying database of members.